Towards designing and measuring interpretable hierarchical fuzzy systems - Razak, Tajul Rosli (2020)
This thesis presents a detailed study of the interpretability of hierarchical fuzzy systems (HFSs). It focuses on the development of a design guidelines framework for interpretable HFSs. This thesis aims to fill some of the gaps in the body of knowledge. Several research questions are raised, including: “How can the interpretability of HFSs be measured with indices?”, “How can complexity be comprehensively measured in HFSs?”, “How can user perception on the interpretability and complexity of HFSs be captured?” and “How can interpretable HFSs be designed?” Thus, to study the interpretability of HFSs, this thesis includes the following methodology discussed in different chapters.